Evaluation of Effectiveness of the TOEFL ITP Short Course Test Program at CLT Unika Soegijapranata on Obtaining The Expected Score - Michael Jonathan Soetjipta (Soegijapranata Catholic University, 2023)
In the current era of globalization, proficiency of foreign languages in specifically English can lead to success. Even though many people learn English and in particulaly TOEFL which is one of the prerequisites for applying scholarship and higher degree of education, many still find difficulty to do TOEFL test. As a result, many get TOEFL score below their expectation. CLT Unika Soegijapranata, an institution appointed to administer the official TOEFL ITP, initiated a short course program for the TOEFL ITP test. This study aims to measure effectiveness of the TOEFL ITP short course program regarding to the achievement of scores. The research used descriptive quantitative in which questionnaire was used to acquire primary data. The results show that the TOEFL ITP short course program is quite effective since it can help the participants to get TOEFL score above 500. CLT Unika Soegijapranta can continue to innovate for this program remains relevant amidst an increasingly massive era.